Exploratory conformational analysis of N-acetyl-L-tryptophan-N-methylamide. An ab initio study - Ceci, María L. (2003)
The full conformational space of N-acetyl-L-tryptophan-N-methylamide was explored by ab initio MO computations. On the Ramachandran hypersurface of four independent variables E = E(φ, Ψ, χ1, χ2), 36 conformers were located instead of the expected 34 = 81 stable structures. The relative stabilities of the various conformers were analyzed in terms of sidechain-backbone interactions. A comparative study amongst theoretical calculations and experimental (NMR and X-ray) results was carried out.